Implications of Flexible Learning to Politics and Economics of Educational Management - Juvelyn Salvador (JPAIR Institutional Research Journal)
This study determined the impact of flexible learning on the politics and economics of educational management. This was conducted to unveil challenges and opportunities encountered by teachers, their implications on the politics and economics of educational administration, and proposed solutions. This was shown on all nine secondary school principals in Zone 3, Division of Catanduanes, Philippines using mixed methods with complete enumeration. The “serious problems” dealt with challenges of the scarcity of supplies and more time printing modules (3.67%), monitoring student’s learning on the difficulty in validating performance (3.89%), difficulty in tracking students (3.78%), and teacher’s health risk (3.56%); retrieval of modules like late submission; checking and evaluating on the difficulty in validating performance and low passing rate. For feedbacking, poor internet connection, and poor parental support. The opportunities for teachers are quality time with family, good savings, and sound health, and very less on developing professionalism like innovating and improving expertise in ICT. The conclusions drawn were the majority are “aged professionals” who do not prioritize higher studies”; 11 years more in service, and most participated in “division level trainings” only. The impact on economics reveals a scarcity of resources that caused teachers to spend personal money; capital outlay funds were spent on printing machines. For politics, it forged strong partnerships among stakeholders for support from LGU and community and private organizations.